Efficacy and safety evaluation of mixed nutrition for postoperative esophageal cancer patients in China: a meta-analysis - Liu, Shui; Qiao, Lin; Liu, Yang; Liu, Hangmei; Li, Yiwen; Sun, Jingbo; Chen, Wei; Shang, Rongguo; Zhang, Lili; Liu, Xiaochuan (Frontiers in Oncology, 2024)
Objective The purpose of this study was to evaluate the clinical effect of mixed nutrition and parenteral nutrition support on postoperative patients with esophageal cancer. Method By searching PubMed, Web of Science, Cochrane, CNKI, Wanfang and other databases, all the literatures until March 2024 about the comparison of randomized controlled Trial (RCT) of mixed nutrition and parenteral nutrition support in postoperative patients with esophageal cancer were screened. The inclusion criteria were that the patients were from randomized controlled trials or clinical trials in China, and the patients were all diagnosed with esophageal cancer by pathological biopsy. The exclusion criteria were the literature other than the above, including repeated published literature, non-Chinese and English literature, incomplete or missing analysis data, etc. After two researchers independently screened the literature, extracted the data and evaluated the risk of bias according to the criteria, Meta-analysis was carried out with RevMan 5.4 software. Results A total of 11 studies were included, including 1216 patients. Meta-analysis showed that, compared with parenteral nutrition, mixed nutrition can improve the levels of transferrin, serum albumin, prealbumin and lymphocyte counts in patients with esophageal cancer after surgery, shorten the time of anal recovery of exhaust, defecation and hospital stay after surgery, and reduce the incidence of pulmonary infection, abdominal distension, incision infection and anastomotic fistula, with statistical significance between the two groups (P < 0.05). The heterogeneity of individual results in this study is relatively high, the analysis comes from clinical heterogeneity, and the publication bias is analyzed through Funnel plot. Taking the incidence of lung infection as an example, the results are evenly distributed on both sides of the Funnel plot, and the publication bias has little impact on the results of the study. Conclusion Compared with parenteral nutrition, mixed nutrition can improve the prognosis of postoperative patients with esophageal cancer and reduce the incidence of related adverse events.